Factors That Influence Job Choice at the Time of Graduation for Physician Assistant Students. Issue 1 (March 2019) - Twombly, Lauren Anne; Rizzolo, Denise; Chen, Rong; Kelchen, Robert
Abstract : Abstract: Research and data analysis show that there is a shortage of primary care providers throughout the United States. Physician assistants (PAs) play an important role in health care delivery; however, the percentage of PAs practicing in primary care has dramatically decreased in the past 15 years. The purpose of this study was to identify potential factors that influence PA students' first job choice following graduation from a PA program to determine whether they have a relationship to the choosing of primary care. The 2016 End of Program Survey data were analyzed using a multinominal logistic regression to determine what factors influenced PA students' selections of primary care as their first job choice: individual factors, program factors, and external factors. Of the 3038 subjects, 269 (8.9%) accepted a job in primary care, 847 (27.9%) accepted a specialty job, and 1922 (63.3%) did not accept a job. When comparing no job accepted versus primary care job choice, marital status and racial/ethnic differences influenced first job choice. Financial factors were also found to be significant predictors. In the second model, comparing specialty versus primary care job choice, marital status influenced first job choice along with financial factors. In addition, one program variable (moderate clinical rotation experience) was found to be statistically significant in the model of specialty versus primary care job choice. Financial factors were found to be the greatest predictor in first job choice. Focusing on policy to help reduce student debt and increase reimbursement rates could help increase the number of students choosing primary care.